Secret of the slight edge - "Moawad, Bob" (New Delhi, 2008)
What is the small difference that makes all the difference? What is the difference between high achievers and low achievers? What are the fudamentals that guarantee a happy and fulfilling life? What is the number one asset inside any organisation that determines its success? Many people have posed these questions and others like them for years. Finally, after helping millions of people unleash their power and the potential of everyone around them Bob Moaward has teamed up with friend and author T.J. Hoisington to share the answers in this book. The Secret of the Slight Edge offers powerful principles and inspirational stories to help people overcome obstacles in their lives and attain their goals. Illustrated with thought-provoking examples and excercises, you will discover that you have unbelieveable potential. You will learn that your thoughts play a central role in what you achieve and that having "the 'right' attitude is everything."
Keywords: Psychology